ANALISIS KONSEPSI PERALIHAN HAK ATAS TANAH HARTA BERSAMA (GONO GINI) MELALUI AKTA HIBAH TERHADAP PIHAK LAIN - Sholihan, Sholihan; Munir, Ahmad; Kuncoro, Cipto; Wulan, Dewi Nawang; Nugroho, Akhmad Dwi Prasetyo (LPPM UNISDA, 2024)
Law Number 1 of 1974 concerning Marriage actually does not provide a loophole for divorce because divorce has consequences not only related to the status of husband, wife, and children but also to property obtained in marriage. This study aims to examine the importance of joint property institutions regulated in positive law in Indonesia and whether the deed of land title grant from joint property made by a Notary and PPAT can be withdrawn by the grantor. This research is a normative legal research using a statutory approach and a concept approach. Based on the results of the discussion, it can be concluded that the importance of the institution of joint property is regulated in positive law in Indonesia because, in its development, the division of joint property after divorce decided by the court is not always divided in half, but also considers the contribution of the husband and wife in their domestic life. Land rights from joint property that belong to widowers or widows can be transferred to other parties by way of grants, and an authentic deed (Notarial Deed) is made. In principle, grants cannot be revoked or cancelled, but there are exceptions, for example, if the grantee does not meet the conditions of the grant.